ANALISIS KUALITAS PERANGKAT PEMBELAJARAN FISIKA SMA BERDASARKAN KURIKULUM 2013 (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This study analyzes the physics learning tool at high school grade X based curriculum 2013 that consists of nine Basic Competencies. The analyzed learning tools are lesson plan, student worksheet and assessment instruments of learning results. The learning tools are prepared by teachers of school that implements curriculum 2013. The assesment uses assessment sheets of lesson plan, student worksheet, and assessment instruments of learning results. The quality of learning tool is determined by the obtained scores from the assessment results, if the scores obtained equal to or bigger than 70 the learning tools are qualified. The analysis result shows that lesson plan, student worksheet and assessment instruments of learning results obtained score below 70. Thus the physics learning tools at high school grade X are less qualified for all Basic Competencies.Keywords: learning tools , curriculum 2013